Implications of Paul's Hopes for the End of Days for Jews and Christians Today: A Critical Re-evaluation of the Evidence - Cunningham, Philip A.; Nanos, Mark D. (Studies in Christian-Jewish Relations, 2014)
In the past decade or so, Paul’s ideas about the eschaton as expressed in Romans 11 have been invoked in a lively discussion about why the Catholic Church today does not organize campaigns to convert Jews to Christianity. Particularly important have been his words about “the full number of the Gentiles.” This essay asks if Paul’s letters require, or support as most appropriate today, a triumphal Christian expectation that at the end of days Jews will inevitably admit that they had been wrong all along in saying “no” to the Christian proclamation of the Gospel. It suggests that a crucial factor is whether Christian readings of Romans 11 today—as well as typical translations of Romans 11—are predicated on a view of Paul as an apostate who departed from Judaism. It argues that current actualizations of Pauline eschatology are quite different if Paul is instead understood as an apostle to the nations from within Judaism. It concludes that present-day eschatological scenarios need to have greater complexity than simplistic zero-sum phrases like “a Jewish turn to Christ” or “Christians will see their error,” and that Paul himself—in a very different religious world—tried to resist such binary thinking when it came to Jews and non-Jews.